PROGRAM PENGABDIAN MAHASISWA: ASISTENSI MENGAJAR DI UPT SD NEGERI 068003 PERUMNAS SIMALINGKAR TAHUN AJARAN 2024/2025 - Sari HS, Dyan Wulan; Sitorus, Irmatansy Alodya; Sembiring, Agnes Salsalina Br; Tarigan, Chindi Clodiya Br; Karo, Jumpa Kita Agata Purba; Sembiring, Josua; Laia, Remigius Relius (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
The Teaching Assistance Program at UPT SD Negeri 068003 Perumnas Simalingkar aims to develop the pedagogical, professional, social, and personal competencies of prospective primary school teachers through direct involvement in instructional and school administrative activities. This study employed a descriptive qualitative approach, using observation, interviews, and documentation over a 13-week period. The results indicate that students successfully designed and implemented 21st-century learning innovations, integrated educational technology, and engaged in non-academic activities such as library management, school discipline monitoring, and extracurricular programs. The program also fostered the development of students’ soft skills and cognitive abilities, despite some challenges in advanced technology use and classroom management. This program has shown a positive impact on improving educational quality at the partner school and provided valuable experiential learning for student-teachers in preparing for professional teaching careers.